Клад. Приклад. 90 некрологов - Угрюмов Владимир Борисович (Жесткий роман, 2005)
Экземпляры: ф.6 (20161021) / Инвентарный номер: 1943 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44